Interaction Between The Ideal Self, Motivation, Academic Goals And Academic Adaptation Towards The Nurse Graduation Competency Test - Nur, Muhammad; Yudhastuti, Ririh; Subarniati, Rika; Melaniani, Soernarnatalina (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Nurse competency test passing rate in Indonesia is still below expectations. There is a correlation between GPA at graduation index. However, there is a similar trend between graduation with underachievement and failure indices with higher GPA. It requires a separate study in addition to the theory and practice of academic ability, need to review internal factors themselves students. This study aimed to analyze the influence of the ideal self, motivation, goal, ability, academic performance and adaptation of learning on nursing graduation competency test. Using a cross sectional design study on a number of 119 new graduates of nursing students from two universities in Makassar, Indonesia during July-November 2017. Selected with probability sampling technique using systematic random sampling. Variable observed; ideal self, academic goals, motivation, learning adaptation, academic ability, and competency test graduation. Analysis of bivariate data using Pearson and Spearman Correlation, and Logistic and Linear Regression for multivariate analysis. The results showed that the ideal self has a positive correlation with academic purposes (rs = 0.240, p = 0.008) and motivation (rs = 0.211, p = 0.021). Multiple linear regression analysis showed that motivation (p = 0.019) and academic purposes (p = 0.000) had a significant influence on adaptation study. Multiple logistic regression test showed that the adaptation of study (p = 0.037), and the theory of academic ability (p = 0.024) had a significant effect on the graduation competency test. Graduates nurses must have a corresponding ideal self to improve motivation. Motivation directing and encouraging learning behaviors that affect graduation competency test. Academic goal setting directs graduates to adapt the learning process. Competence of graduates is not enough with just a written test that predicted by the theory of academic ability, but needs to be equipped with a practice test.